Is Halal Certification Able to Affect Consumer Behavior in Buying Food Products? - Nur Fadillah; Muhammad Hasby (Management Department Universitas Islam Negeri Sumatera Utara, 2021)
This research is motivated by the habits of the people of Indonesia, which often use the products being sold but need to pay more attention to matters of halal certification, which often does not include a halal label. These habits can endanger everyone because, in the end, everyone will be free to sell goods or food and can buy anything regardless of the halalness of a product, especially food products and other products. This study uses a qualitative literature study method, namely by looking at the phenomena that occur and previous research. This research will show how consumers can behave to improve their awareness when buying a product closely related to halal, be it a food product (which is consumed) or other products (used or used). This research aims to make consumers aware that they still prioritize halal rather than interest in a product that will be purchased, used, and even consumed, whose benefits are not only for the individual but for everyone or the good of many people. Furthermore, by increasing awareness, we can carry out our daily lives to be more actual and more on target while remaining in the corridors of goodness and benefit.Keywords: Awareness, behavior, food product, halal.